Dinamika Uang Panai’ di Kota Makassar Pasca Fatwa MUI Sulawesi Selatan No. 2 Tahun 2022: Menakar Kepatuhan Syariah dan Pelestarian Tradisi - Nasmi, Nasmi; Bakry, Muammar; Haddade, Abdul Wahid; Salam, Abdul (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2025)
This study aims to analyze the influence of the Fatwa of the Indonesian Ulema Council (MUI) of South Sulawesi No. 2 of 2022 on panai' money and its implications for Bugis marriage practices in Bangkala Village, Manggala District, Makassar City. The subject matter of this research focuses on how the implementation of the fatwa on the tradition of panai' money in Bugis society. This research uses a qualitative approach with a descriptive-analytical method. Data were collected through in-depth interviews with traditional leaders, scholars, and the community, participatory observation, and documentation of the fatwa text and related social practices. The results show that panai' money still has an important position in the traditional structure of the Makassar Bugis community and is seen as a form of respect and a symbol of the man's social responsibility towards the woman. Although the fatwa of MUI South Sulawesi states that panai' money is a custom whose law is permissible as long as it is not burdensome, its implementation in the community has not shown significant changes. The lack of socialization and education from religious institutions and related parties is a factor inhibiting the understanding and application of the contents of the fatwa as a whole. The implication of this finding is that the preservation of customary values must be accompanied by a proportional understanding of Sharia so that tradition does not become a barrier to marriage. Intensive cultural and educative approaches are needed so that this fatwa can be accepted and implemented by the community in accordance with moderate and contextual Islamic values.